1995
DOI: 10.1073/pnas.92.11.4728
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of the agouti gene in transgenic mice causes obesity, features of type II diabetes, and yellow fur.

Abstract: Mice that carry the lethal yellow (AY) or viable yellow (AVY) mutation, two dominant mutations of the agouti (a) gene in mouse chromosome 2, exhibit a phenotype that includes yellow fur, marked obesity, a form of type II diabetes associated with insulin resistance, and an increased susceptibility to tumor development. Molecular analyses of these and several other dominant "obese yellow" a-locus mutations suggested that ectopic expression of the normal agouti protein gives rise to this complex pleiotropic pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
165
1
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(174 citation statements)
references
References 39 publications
5
165
1
3
Order By: Relevance
“…In all cases, a heterologous promoter causes the normal agouti protein to be ectopically expressed in a ubiquitous manner (1,(12)(13)(14). We recently confirmed that the ectopic expression of the normal agouti protein is responsible for the obesity and insulin resistance through the production of transgenic mice that express the normal agouti gene from a ubiquitous promoter (18). However, from these experiments, we were not able to distinguish between a ubiquitous, systemic effect or a localized, tissue-specific effect of agouti.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…In all cases, a heterologous promoter causes the normal agouti protein to be ectopically expressed in a ubiquitous manner (1,(12)(13)(14). We recently confirmed that the ectopic expression of the normal agouti protein is responsible for the obesity and insulin resistance through the production of transgenic mice that express the normal agouti gene from a ubiquitous promoter (18). However, from these experiments, we were not able to distinguish between a ubiquitous, systemic effect or a localized, tissue-specific effect of agouti.…”
mentioning
confidence: 70%
“…To generate the aP2 promoter-agouti expression construct, a HindIII-ClaI fragment containing the complete mouse agouti cDNA along with the simian virus 40 polyadenylylation signal sequence was isolated from BAPa (18). This fragment was cloned downstream of the Ϫ5.4 kb to ϩ21 bp fragment of the promoter for the adipocyte P2 (aP2) gene in the pSKIIϩ vector (24).…”
Section: Methodsmentioning
confidence: 99%
“…In litters from Agouti/L mothers, A ypositive and A y -negative offspring are easily distinguished by their distinct coat colors. Agouti/L mice become obese around 6-8 weeks of age [15]. The body weights and blood glucose levels of Agouti/L and L mothers are shown in Table 1.…”
Section: Animalsmentioning
confidence: 99%
“…Dominant mutations of the mouse ASP gene or the production of transgenic mice that ubiquitously express ASP from the human b-actin promoter will lead to a pleiotropic 'yellow obesity' syndrome. 24 Yellowing is the result of chronic binding of ASP to MC1R, and the obese, hyperglycaemic phenotype may be due to the interaction between ASP and MC4R. However, in a transgenic mice model using the melanocyte-specific TYRP1 gene promoter and keratinocyte-specific keratin-14 gene promoter to limit ASP gene expression in mouse skin, the overexpressed agouti protein enables the fading of mouse coat colour phenotype, while leaving the characteristics of obesity and hyperglycaemia unaffected.…”
Section: Seeing the Gene Therapy C-h Yang Et Almentioning
confidence: 99%